Grobstadtkultur. The question of the great town in Germany under the kaiser William rule (Ciudades, 2018)
This article analyzes the conflictive relationship between the different intellectual tendencies (and social blocs) in the Germany of the change of century and, the great modern town (Groβstadt). The study of the Groβstadt by authors like: Tönnies, Nietzsche, Simmel, Naumann, Tesenow, Sombart o Weber, among others, allow us to establish four moments in this relationship: conflict between intellectual work and capitalist economy expressed in the Groβstadt gestation, attempts of synthesizing both factors from the culture and from the capital, nostalgic review of the small industrial town (Kleinstadt), and last but not least, the abandon of the ideological principles in the interest of a technical reform oriented to solve the Groβstadt problems.
Keywords: Great German Town (Groβstadt); end of century German culture; Tönnies; Nietzsche; Simmel; Naumann; Tessenow; Sombart; Weber